Efficient hydrogen liberation from autocatalytic wastewater treatment by green synthesized Ag2SeO3 nanocatalyst - Islam, Sk Najrul; Ansari, Ifra Ilyas; Gopinath, Chinnakonda S.; Ahmad, Absar (Inorganic Chemistry Communications, 2025)
Concerns about wastewater management, secure hydrogen storage, and interest in an affordable, effective, and user-friendly technique for releasing hydrogen have grown globally. Developing sustainable synthetic processes that result in industrially significant nanocatalyst to synergistically accelerate the evolution of hydrogen from wastewater treatment is extremely desirable. This work, for the first time, demonstrates the design and green fabrication of bactericidal silver selenite nanoparticles (Ag2SeO3 NPs) using the fungus Aspergillus niger for autocatalytic hydrogen production and methylene blue dye reduction by hydrolytic dehydrogenation of NaBH4. The morphology of Ag2SeO3 nanocatalysts with an average particle size of 60 nm was assessed by FETEM, while their surface chemistry, crystal structure, and optical properties were examined using XPS, XRD, and FTIR/ UV-Visible spectrophotometers, respectively. The sigmoidal trajectory of NaBH4 dehydrogenation with turnover frequencies (TOF) of 4750 mL g- 1 min- 1 suggested good autocatalytic activity of Ag2SeO3 NPs. The mechanistic study unveiled that autocatalysis was made possible by the creation of novel, active Ag co-catalyst which works synergistically with Ag2SeO3 NPs. For in-situ, real time assessment of Ag concentration during catalysis, hydrolysis of NaBH4 was carried out in the presence of methylene blue dye. The results showed that the active cocatalyst centers have a significant influence on autocatalytic hydrogen production at room temperature, reducing 98.8 % methylene blue (MB) dye in 6 min with a lesser hydrogen generation rate of 4174 mL g- 1 min- 1. The catalyst exhibited excellent stability and durability after fourth consecutive cycle, demonstrating its promise for long-term and recurring application in hydrogen liberation from autocatalytic MB dye reduction.
Keywords: Ag2SeO3 nanoparticles; Antibacterial; autocatalysis; Hydrogen generation; Wastewater treatment